Analysis of geosynthetic reinforcement in pile-supported embankments. Part III: Axisymmetric model. Issue 2 (April 2010) - Plaut, R.H.; Filz, G.M.
Abstract : ABSTRACT: In the first part of this study, the geosynthetic reinforcement in a pile-supported embankment was modelled as a thin plate, and in the second part it was modelled as a cable net. Three-dimensional analyses were conducted. A notable feature of the results was the existence of spikes in strains and stresses near the edges of the pile caps, particularly near corners. The computational effort was significant. In this last part an axisymmetric model is analysed, which is simpler, and yields approximate results. It is most appropriate for circular pile caps, but can also be used to estimate displacements for square pile caps. The geosynthetic is modelled here as a membrane with linear stress–strain response, and the governing equations allow for large strains and slopes. The finite difference method is utilised, and the total energy is minimised to obtain equilibrium shapes. For two cases, the effects of Poisson's ratio, soil stiffness, stress concentration ratio, average embankment stress, area replacement ratio and membrane stiffness on the maximum vertical displacement, maximum strains and net stress reduction ratio are determined. A Rayleigh–Ritz procedure is also carried out. Finally, determination of the magnitude of the applied stress on the geosynthetic and the effect of its distribution are discussed.